2008
DOI: 10.1128/aac.00117-08
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Acquisition of Fluoroquinolone-Resistant Gram-Negative Bacilli in the Intestinal Tracts of Mice Treated with Fluoroquinolone Antimicrobial Agents

Abstract: After mice received orogastric administration of a fluoroquinolone-resistant Klebsiella pneumoniae strain, subcutaneous treatment with ciprofloxacin, levofloxacin, and moxifloxacin promoted persistent low-density colonization in 10% to 40% of the mice, whereas treatment with clindamycin consistently promoted highdensity colonization. No emergence of fluoroquinolone-resistant gram-negative bacilli was detected in the mice during or after treatment with the fluoroquinolone antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…These results are in concordance with data from previous studies using animal models which showed that antibiotics that do not disrupt the anaerobic microflora may be less likely to promote colonization with MDR Gram-negative bacteria (6,23). In humans, stool concentrations of cefepime have been estimated to be extremely low, while concentrations of ciprofloxacin vary widely (from undetectable to 858 g/g) (4,28).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are in concordance with data from previous studies using animal models which showed that antibiotics that do not disrupt the anaerobic microflora may be less likely to promote colonization with MDR Gram-negative bacteria (6,23). In humans, stool concentrations of cefepime have been estimated to be extremely low, while concentrations of ciprofloxacin vary widely (from undetectable to 858 g/g) (4,28).…”
Section: Discussionsupporting
confidence: 82%
“…The antibiotic dosages and dosing frequency that were used do not mimic systemic exposures in patients. However, we previously found that the administration of equivalent doses (mg/kg) to mice once or twice daily results in levels of drug in stool and effects on the intestinal microflora that are similar to those seen with healthy human volunteers (6,22,23). In the current study, the concentrations of antibiotics in stool samples of mice and the degree of alteration of the microflora are consistent with data from previous studies of human volunteers or patients (4,17,21).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the first using a model of natural gut colonization by pathogenic bacteria from a nonintestinal infection site and showing the emergence of resistant strains in this new intestinal population during fluoroquinolone treatment of a lung infection. Indeed, usually studies on intestinal colonization use orogastric gavage of bacteria already resistant to the antibiotic (6,14).…”
Section: Discussionmentioning
confidence: 99%
“…We used a well-established murine model (23)(24)(25)(27)(28)(29)(30)(31)(32)(33) to test intestinal colonization resistance to VRE. Mouse groups 1 and 3 received oral gavage with 0.5 ml of normal saline (NS) alone once/day for 3 days, delivered via a stainless steel feeding tube (Perfektum; Popper and Sons), as their microbiota was recovering from the piperacillin-tazobactam.…”
Section: Bacterial Strainsmentioning
confidence: 99%